(untitled) (Experimental biology, 2015)
NK cells education is an intensively studied field of immunology. In mice Ly49 receptor-H-2 class I interactions and KIR-MHC I in human mediate this process. NK cells bearing self-MHC specific inhibitory receptors are “licensed (L)” and lacking them are “hyporesponsive (HR)”. HR state can be reversible upon certain conditions. The role of HR NK cells in defence against cancer stem cells (CSC) was not investigated. HR NK cells have features making them more potent for this purpose compared to licensed counterparts. A mouse model to study NK cell education in vivo is described here, where Ly49 ligand binding ability and the influence on target cell lysis is unified. At least four types of mice can be a basis for many experimental designs. Mouse model is proposed to be applied to study the processes of HR NK cell involvement in CSC eradication.